SOLUSI PANGAN BERKELANJUTAN ATAU ANCAMAN EKOLOGI? MENIMBANG PRAKTIK PERLADANGAN BERPINDAH - Dhonanto, Donny; Darma, Surya; Mulyadi, Mulyadi; Imang, Ndan; Fahrunsyah, Fahrunsyah; Nurhasanah, Nurhasanah; Paranoan, Ria Rachel; Salsabila, Ghaisani; Nugroho, Bagus Adi (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Shifting cultivation is a traditional agricultural practice that has been carried out by Indigenous communities across tropical regions for thousands of years. Although this system is characterized by land rotation and slash-and-burn techniques, it has become a subject of debate in the context of sustainable food security and environmental threats. This study aimed to analyze the controversy surrounding shifting cultivation as a potential solution for sustainable food security, as well as its ecological and socio-economic impacts. The method employed in this research was a Systematic Literature Review (SLR). The findings indicated that shifting cultivation had dualistic impacts. On one hand, it could lead to deforestation and significant carbon emissions, particularly when fallow periods were less than ten years, resulting in the loss of up to 80% of forest carbon stocks. On the other hand, when practiced with long fallow cycles (15–30 years), shifting cultivation could support the regeneration of natural ecosystems and restore up to 50% of forest carbon reserves. Furthermore, shifting cultivation contributed to the food security of Indigenous peoples through crop diversification and the preservation of local ecological knowledge in biodiversity conservation. Shifting cultivation represented an adaptive strategy for Indigenous communities in managing natural resources. As a food production system, it held sustainability potential when aligned with natural cycles and grounded in traditional knowledge. Its environmental impact largely depended on the manner of implementation, damaging when mismanaged, but regenerative when properly applied. Therefore, context-specific and inclusive policies that recognize Indigenous land rights are essential to ensure the positive contribution of shifting cultivation to food security and environmental sustainability.